Strategi Pengembangan Prodi Asuransi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Antasari Banjarmasin dengan Menggunakan Analisis QSPM (Quantitative Strategic Planning Matrix) - Lutpi Sahal; Rimayanti Rimayanti; Elida Mahriani; M. Ferry Hidayat (Islamic Economics and Business Faculty of UIN Antasari, 2023)
There are only 3 PTKINs in Indonesia that have opened a Sharia Insurance Undergraduate study program, including UIN Antasari Banjarmasin. Regionally, in Kalimantan, this is the only study program within PTKI. So far, the study program has established cooperation in the form of student apprenticeships, while in the form of professional training is very limited. Therefore, it is necessary to know more about the expectations of external stakeholders for the Sharia Insurance Study Program, especially regarding the competency of alumni needed by the Sharia insurance industry, internal and external factors that need to be considered in the development of the study program, then also how to develop an appropriate study program development strategy with the development of the world of work. This research is quantitative research with a descriptive approach. The data analysis methods are IFE, EFE, IE, SWOT, and QSPM Matrix. The results have shown that the competencies needed by the insurance industry to increase the absorption of alumni in the world of work, among others, for students in the form of soft skills and hard skills, the ability of lecturers to combine theory and practice during the learning process, for study programs to increase the availability of learning facilities and infrastructure both in quantity and quality, cooperate with UPKK UIN Antasari & alumni, and take advantage of cooperation agreements with hospitals & insurance. The strategy for developing the Sharia Insurance Study Program of the Faculty of Economics and Islamic Business using QSPM (Quantitative Strategic Planning Matrix) analysis is in quadrant II, namely market penetration and product development strategies.